Eksistensi Kebaya Ready To Wear pada Masa Pandemic COVID 19 di Bali - Dewa Ayu Putu, Leliana Sari (Jurnal Bali Membangun Bali, 2022)
This paper aims to determine the existence of ready-to-wear kebayas during the COVID-19 pandemic in Bali. Women as the subject of the driving wheel of Balinese cultural conservationists to stay awake in the era of globalization and modernization. One form of traditional Balinese clothing worn by women to carry out all forms of prayer is the kebaya. The development of the kebaya into a symbol of the social status of women in Bali. Balinese women's kebaya is worn and viewed in terms of neatness, compatibility, and adjusted for what event/occasion, how to wear it, and when the kebaya can be used. The method used is descriptive qualitative, which is carried out by reviewing the literature in the form of books, journals, and online media such as Facebook, and Instagram of kebaya producers/traders to find out the models or designs of ready-to-wear kebayas that are trending during the current pandemic. Efforts kebaya are being made such as events/activities that support the Indonesian Cultural Conservation Women Community by bringing back the post-covid-19 pandemic through the Balinese kebaya. There is The Indonesian Berkebaya Movement community movement with the national identity kebaya theme, as well as fashion industry producers. Especially traditional clothing, making breakthrough such as ready-to-wear kebaya, with the advantage of being ready to use with a choice of various sizes S, M, L to XXL (big size), the price is more affordable than custom made according to your size at a private tailor (fabric price plus sewing costs).